Large area inkjet-printed metal halide perovskite LEDs enabled by gas flow assisted drying and crystallization. Issue 12 (1st March 2023) - Schröder, Vincent R. F.; Fratzscher, Nicolas; Mathies, Florian; Nandayapa, Edgar R.; Hermerschmidt, Felix; Unger, Eva L.; List-Kratochvil, Emil J. W.
Abstract : Large area metal halide perovskite LEDs were fabricated by inkjet printing. Homogeneous drying and crystallization was facilitated by a guided and optimized gas flow. Abstract : We demonstrate the upscaling of inkjet-printed metal halide perovskite light-emitting diodes. To achieve this, the drying process, critical for controlling the crystallization of the perovskite layer, was optimized with an airblade-like slit nozzle in a gas flow assisted vacuum drying step. This yields large, continuous perovskite layers in light-emitting diodes with an active area up to 1600 mm 2 .